Postface: The Laurentide Ice Sheet : Research Problems - Andrews, John (Géographie physique et Quaternaire, 1987)
ABSTRACTAlthough major progress has been made in several research topics on the Laurentide Ice Sheet, there are still substantial problems that require investigation over the next decade. Of particular importance will be the active participation between modelers and those who provide the "ground truth". Although individual reconstructions of the ice sheet, based on glacial isostasy, glaciology, climatology, and glacial geology, will continue to be developed and refined the next important step should be the development of an integrated climate/glaciology/isostatic ice sheet reconstruction that will serve to provide a holistic series of predictions about glacial, glacial marine, and periglacial landforms, sediments, and chronologies. These predictions can then serve as the basis for guiding field programs to examine bedforms and sediments associated with this ice sheet. This program of model reconstruction and verification will require a more complete understanding of glacial depositional processes than is currently available and, in addition, will be heavily dependant on a detailed dating program to improve our knowledge of the chronology of events.